Calibrated ages of Pulpito (PUL-14) peat core from Patagonia - Thomas P Roland (PANGAEA, 2021)
Calibrated ages of a high-resolution peat core from the Past Global Changes - Carbon in Peat on EArth through Time (PAGES_C-PEAT) Project.